Liderazgo transformacional y desempeño docente en el Cepre de la Universidad Nacional del Centro del Perú - De la Cruz Sullca, Pepe Raúl (2018)
This research had as objective to describe the influence of transformational leadership on the teaching performance at the Pre-University Center of the Universidad Nacional del Centro del Perú (Cepre-UNCP, by its acronym in Spanish). It was used the methodology of scientific research, whose specifications are: basic type, descriptive-correlational level and non-experimental transversal design. The sample was composed of 50 teachers from the Cepre-UNCP, who were administered a questionnaire survey. The results obtained indicate that the influence of transformational leadership on the teaching performance at the Cepre-UNCP is significant. This is because the value of the continuity correction is 45 and the p-value is 0.00, less than 0.05, so we reject the null hypothesis and accept the research hypothesis in the sense that transformational leadership significantly influences the performance of teachers.   DOI: https://doi.org/10.31876/sl.v1i1.2